The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hep.31810
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Transient Elastography in Assessing Fibrosis at Diagnosis in Naïve Patients With Primary Biliary Cholangitis: A Dual Cut‐Off Approach

Abstract: on the behalf of the Italian PBC RegistryBaCKgRoUND aND aIMS: Liver fibrosis holds a relevant prognostic meaning in primary biliary cholangitis (PBC). Noninvasive fibrosis evaluation using vibration-controlled transient elastography (VCTE) is routinely performed. However, there is limited evidence on its accuracy at diagnosis in PBC. We aimed to estimate the diagnostic accuracy of VCTE in assessing advanced fibrosis (AF) at disease presentation in PBC. appRoaCH aND ReSUltS: We collected data from 167 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Among the different techniques available, VCTE (FibroScan  ) was the first to be marketed, has been the most extensively evaluated, and is today one of the most popular and commonly used, especially in hepatology units [14,35]. Prior studies in patients with PBC have shown an association of LSM with histological fibrosis stage, degree of portal hypertension, and risk of death or need for LT [16,17,19,20,[36][37][38]. However, these results are still supported by limited data and a few small-size single-centre studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different techniques available, VCTE (FibroScan  ) was the first to be marketed, has been the most extensively evaluated, and is today one of the most popular and commonly used, especially in hepatology units [14,35]. Prior studies in patients with PBC have shown an association of LSM with histological fibrosis stage, degree of portal hypertension, and risk of death or need for LT [16,17,19,20,[36][37][38]. However, these results are still supported by limited data and a few small-size single-centre studies.…”
Section: Discussionmentioning
confidence: 99%
“…Today, of the various alternative techniques of liver elastography, VCTE remains one of the most popular and widely used worldwide [15]. Liver stiffness measurement (LSM) by VCTE has indeed been shown as a very simple and reliable means for diagnosing cirrhosis or advanced fibrosis in many chronic liver diseases, including PBC [16,17]. It has further been linked to the risk of portal hypertension, cirrhotic decompensation, hepatocellular carcinoma, and liver-related mortality in different liver conditions, including PBC [16,[18][19][20].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 9 Histological staging was performed on all slides according to multiple histological scoring systems and criteria (Ludwig, Nakanuma, Ishak, Scheuer, Metavir). 6,9,10,15 For the purposes of this study, patients were categorized as early (Ludwig I-II) and advanced stage (Ludwig III-IV).…”
Section: Liver Biopsy and Histopathological Evaluationmentioning
confidence: 99%
“…The leading cause(s) of the diverse disease progression have been poorly studied, and few biomarkers are available to follow people with PBC along their clinical course, whereas risk stratification at diagnosis relies only on age, histological stage, signs of hepatic dysfunction and/or portal hypertension, and liver stiffness. 6 , 7 Alkaline phosphatase (ALP) is a marker of cholestasis and bile duct injury and represents the pillar of the ‘UDCA response’ 7 ; the magnitude of its reduction after UDCA therapy relates to long-term outcomes as confirmed by large-scale, observational studies. 8 However, the mechanisms underlying UDCA effects in cholestasis and the heterogeneous response in people with PBC remain to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, there have been many changes in the diagnosis and management of PBC, with more patients being recognized with earlier-stage disease and with the use of the recommended first-line pharmacotherapy, ursodeoxycholic acid (UDCA) (6,7). The use of liver stiffness measurement (LSM), using vibration-controlled transient elastography (VCTE), is now routinely performed in PBC (8,9).…”
Section: Introductionmentioning
confidence: 99%